THE EFFECT OF AI AS AN ONLINE TUTOR AND DIGITAL LITERACY ON LEARNING COMPREHENSION A SEM APPROACH - Guntur Gunawan; Yuyun Yumiarty (Smart Education, 2026)
This study aims to analyze the effect of AI as an online tutor and digital literacy on students’ learning comprehension. The research employed a quantitative approach with an explanatory survey design involving 100 students from the PGMI Study Program at IAIN Curup. The research instrument was a Likert-scale questionnaire measuring three main constructs: AI as an online tutor, digital literacy, and learning comprehension. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to test validity, reliability, and the structural relationships among variables. The results indicate that AI as an online tutor has a positive and significant effect on learning comprehension (? = 0.425; p < 0.000). Digital literacy also has a positive and significant effect on learning comprehension (? = 0.476; p < 0.000). The R-square value of 0.699 shows that 69.9% of the variance in learning comprehension can be explained by these two independent variables. Overall, this study confirms that the integration of AI-based technology, supported by students’ digital literacy skills, can enhance the quality of learning comprehension in higher education.